182k views
2 votes
P(n)=3n+3 find p(-6)2)g(x)=x+4 find g(4)

1 Answer

4 votes

Final answer:

To find P(-6), substitute -6 into the function P(n) to get -15. To find g(4), substitute 4 into the function g(x) to get 8.

Step-by-step explanation:

The student is asking about evaluating polynomial and linear functions at specific inputs. The given functions are P(n) = 3n + 3 and g(x) = x + 4. To find P(-6), we replace 'n' with -6 in the polynomial function. For g(4), we replace 'x' with 4 in the linear function.

  • To calculate P(-6): P(-6) = 3(-6) + 3 = -18 + 3 = -15.
  • To calculate g(4): g(4) = 4 + 4 = 8.

User Jason Stirk
by
5.1k points